Acute Cellular Rejection Presenting With Sinusoidal Obstruction Syndrome and Refractory Ascites Postliver Transplantation. Issue 1 (27th January 2023) - Harris, Elizabeth; Hanish, Steven; Vagefi, Parsia; Mufti, Arjmand
ABSTRACT: Sinusoidal obstruction syndrome (SOS) is a rare cause of ascites postliver transplantation. We describe the case of a 21-year-old woman transplanted for glycogen storage disease type 1a who developed ascites posttransplantation and was determined to have SOS in the setting of acute cellular rejection (ACR). This case has implications for the management of patients who develop ascites in the setting of ACR postliver transplantation. To our knowledge, this is the only reported case of ACR complicated by SOS in a patient status postliver transplantation for glycogen storage disease type 1a.